Forbidden Nights with the Surgeon - Hawkes, Charlotte (Billionaire Twin Surgeons, 2022)
Flirting with the forbidden! Can they resist their attraction, or will they give in to temptation? Find out in the second story in Charlotte Hawkes's Billionaire Twin Surgeons duet!Will one night......be enough? It's surgeon Rik's first day at Thorncroft Royal Infirmary and his plan is simple: to reunite with his long-lost brother and put the ghosts of their past to rest. Until Rik is reunited with Dr. Grace...who completely derails his plans! Because Grace is not just the woman whom he spent one unforgettable night with--she's his brother's best friend! With a connection this powerful, can they walk away from their off-limits temptation?From Harlequin Medical: Life and love in the world of modern medicine. Billionaire Twin SurgeonsBook 1: Shock Baby for the DoctorBook 2: Forbidden Nights with the Surgeon